The Effect of Consuming Papaya on the Smoothness of Breast Milk in Breastfeeding Mothers in the Working Area of Songgon Community Health Center in 2025 - Palupi, Denok Indah Retno; Purnamasari, Desy; Hakiki, Miftahul (STIKes RSPAD RSPAD Gatot Soebroto, 2025)
AbstractBreast milk is the primary source of nutrition for newborns and plays a crucial role in infants' growth and immune system. However, smooth breast milk production is often a challenge for some breastfeeding mothers. One non-pharmacological effort that can support smooth breast milk production is consuming Papaya. Papaya contains lactogagum, which can secrete oxytocin and prolactin, hormones that stimulate breast milk production. This study aimed to determine the effect of papaya consumption on smooth breast milk flow in breastfeeding mothers in the Songgon Community Health Center working area in 2025. This study implemented a quasi-experimental design through a pre-test and post-test approach. 30 respondents were obtained through accidental sampling, which was divided into 2 groups, 15 intervention group respondents and 15 control group respondents, thus meeting the minimum number of samples suitable for the study. The intervention group was given papaya fruit 3 times a day for 7 days with a dose of 250 grams at each meal. The control group was not given any treatment. The sampling technique used was accidental sampling. The instruments used were a questionnaire indicator of smooth breast milk flow and an observation sheet. Data analysis was conducted using the Wilcoxon and Mann-Whitney tests using SPSS 25 for Windows. The study was conducted on January 31–February 25, 2025, with KEPK No. 071/01/KEPK-STIKESBWI/I/2024-2025. The results showed that the average smoothness of breast milk in the intervention group increased from 1.87 to 7.40, while the control group increased from 2.20 to 4.00. The average difference between the intervention group was 5.53, and the control group was 1.8. The p-value = 0.000 indicates an effect. Papaya can be recommended as a natural alternative to increase breast milk flow. Keywords: Breastfeeding Mothers, Breast Milk, Papaya, Smoothness of Breast Milk